#TITLE_ALTERNATIVE# - FAIZAL ZAKARIA (NIM : 22310301); Pembimbing : Dr. Hendra Grandis, MUHAMMAD
A magnetotelluric (MT) survey was performed at Lili Geothermal Field, Polewali Mandar, West Sulawesi to assess the geothermal system in this area. The data were acquired at 31 measurement points distributed into 5 lines. Inverse modelling was performed using WinGLink software to obtain the resistivity section of the sub-surface. Low resistivity from 2-D MT modelling interpreted as a caprock exist from surface to 1000 m depth. Therefore the top of reservoir is at 1000 m depth with varying thickness from 500 m to 1000 m. The area of geothermal prospect is approximately 33 km2 with potential reserve estimated of 86 Mwe.